2020
DOI: 10.1101/2020.09.18.304022
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanism of selectivity reveals novel antifolate drug interactions

Abstract: Antimicrobial agents that target a specific pathogen of interest is the gold standard in drug design. para-Aminosalicylic acid (PAS), remains a cornerstone therapy, in the treatment against Mycobacterium tuberculosis, owing to its high level of selectivity. Despite its high level of selectivity, PAS has been reassigned to treat drug-resistant strains of M. tuberculosis because it causes severe gastrointestinal (GI) distress that results in poor patient compliance. We have previously shown PAS inhibits the fola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…One last remark, PAS exerts antimicrobial activity characteristically against Mtb strains and not any other bacteria as the latter can utilize PAS as a surrogate of PABA in the folate biosynthesis pathway. This fact explains the in vitro activity of title compounds against Mtb but not against other bacteria and in return strengthens the argument that DHFR is their molecular target …”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…One last remark, PAS exerts antimicrobial activity characteristically against Mtb strains and not any other bacteria as the latter can utilize PAS as a surrogate of PABA in the folate biosynthesis pathway. This fact explains the in vitro activity of title compounds against Mtb but not against other bacteria and in return strengthens the argument that DHFR is their molecular target …”
Section: Resultssupporting
confidence: 76%
“…This fact explains the in vitro activity of title compounds against Mtb but not against other bacteria and in return strengthens the argument that DHFR is their molecular target. 23 In Silico Binding to Mycobacterial DHFR Our biochemical studies indicated that compound 11 inhibits the DHFR activity in Mtb H37Ra on the whole-cell level. To assess the possible binding of 11 to mycobacterial DHFR, we performed molecular docking to pdb id: 5u26, representing the most common conformation of Mtb DHFR in the PDB database.…”
Section: Complementation Of the Antimycobacterial Activity By Methioninementioning
confidence: 90%